Multiple metabolic innovations and losses are associated with major transitions in land plant evolution - Cannell, N; Emms, DM; Hetherington, AJ; MacKay, J; Kelly, S; Dolan, L; Sweetlove, LJ (Cell Press, 2020)
Investigating the evolution of plant biochemistry is challenging because few metabolites are preserved in fossils and because metabolic networks are difficult to experimentally characterize in diverse extant organisms. We report a comparative computational approach based on whole-genome metabolic pathway databases of eight species representative of major plant lineages, combined with homologous relationships among genes of 72 species from streptophyte algae to angiosperms. We use this genomic approach to identify metabolic gains and losses during land plant evolution. We extended our findings with additional analysis of 305 non-angiosperm plant transcriptomes. Our results revealed that genes encoding the complete biosynthetic pathway for brassinosteroid phytohormones and enzymes for brassinosteroid inactivation are present only in spermatophytes. Genes encoding only part of the biosynthesis pathway are present in ferns and lycophytes, indicating a stepwise evolutionary acquisition of this pathway. Nevertheless, brassinosteroids are ubiquitous in land plants, suggesting that brassinosteroid biosynthetic pathways differ between earlier- and later-diverging lineages. Conversely, genes for gibberellin biosynthesis and inactivation using methyltransferases are found in all land plant lineages. This suggests that bioactive gibberellins might be present in bryophytes, although they have yet to be detected experimentally. We also found that cytochrome P450 oxidases involved in cutin and suberin production are absent in genomes of non-angiosperm plants that nevertheless do contain these biopolymers. Overall, we identified significant differences in crucial metabolic processes between angiosperms and earlier-diverging land plants and resolve details of the evolutionary history of several phytohormone and structural polymer biosynthetic pathways in land plants.